The genome sequence of the Fan-foot, Herminia tarsipennalis (Treitschke, 1835) - Boyes, D; Holland, PWH (F1000 Research Ltd, 2023)
We present a genome assembly from an individual male Herminia tarsipennalis (the Fan-foot; Arthropoda; Insecta; Lepidoptera; Erebidae). The genome sequence is 788.4 megabases in span. Most of the assembly is scaffolded into 30 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 17.12 kilobases in length.